Spectroscopic Study of Cytosine Methylation Effect on Thermodynamics of DNA Duplex Containing CpG Motif - Václav Římal; Ondřej Socha; Josef Štěpánek; Helena Štěpánková (Journal of Spectroscopy)
Effect of cytosine methylation on DNA duplexes was studied by using a model system of three self-complementary DNA octamers containing central CpG motif surrounded by a couple of AT base pairs, CAACGTTG, CATCGATG, and CTTCGAAG, and their analogues with the central cytosine methylated at C5 position. Temperature dependences of 1H NMR, UV absorption, and Raman scattering spectra measured for aqueous solutions at concentrations of different orders of magnitude were subjected to a joint analysis that allowed an accurate determination of the enthalpy and entropy of duplex formation. It was revealed that the changes of the enthalpy and entropy contributions are strongly dependent on the base composition in the vicinity of the CpG motif.